Spirituality in the enterprise - de Paul de Barchifontaine, Christian (O Mundo da Saúde, 2007)
When reflecting on spirituality in enterprises, the author inquires, after some conceptualizations: is it possible to talk of spirituality in enterprises when the current ideology is based on economic globalization and the centrality of economy in detriment of society? We live a crisis of humanism: we need to rediscover the sense of human dignity by making a reflection on how we could develop spirituality in enterprises. After some commentaries, the author suggests that, who knows, economic globalization is helping to discover a new world, affecting the globalization of solidarity.